Correction to: Characterization of a fatty acid-binding protein from the Pacific oyster (Crassostrea gigas): pharmaceutical and toxicological implications - Tisca, Juliana F.; dos Santos, Karin; Pessati, Tomás B.; Zacchi, Flávia L.; Soares, Fabíola S.; Oliveira, Vanessa A.; Bebianno, Maria João; Bainy, Afonso C. D.; Razzera, Guilherme (Environmental Science and Pollution Research, 2021)
info:eu-repo/semantics/publishedVersion